Sidney Sheldon's Mistress of the game - Bagshawe, Tilly (William Morrow, Happer, 2009)
The decendents of Kate Blackwell battle to carry on her powerful legacy. Each is determined to control Kruger-Brent, Ltd., the multibillion-dollar international corporation with holdings in diverse industries around the world. But only one can reign supreme.--From publisher's description.